Does cross-listing signal quality - Durand, Robert; Gunawan, F.; Tarca, A. (Elsevier Ltd, 2006)
The literature on cross-listing generally conveys the impression that cross-listing is good news about a firm. This paper focuses on returns following cross-listing where evidence of positive results from cross-listing is mixed. considering 81 Australian firms, we find that cross-listed firms are less profitable with higher debt levels prior to cross-listing and that they achieve significant negative abnormal returns in the three years following cross-listing. This result holds even for firms seeking the benefits of “bonding” to US disclosure requirements by cross-listing in the more regulated US markets. Our study suggests cross-listing is not an unambiguous positive signal about a firm.